The factors predicting development of serious infections in ANCA-associated vasculitis - Uslu Yurteri, Emine; Sezer, Serdar; Torgutalp, Murat; Yayla, Müçteba Enes; Sahin Eroglu, Didem; Okatan, Ilyas Ercan; Kelesoglu Dincer, Ayse Bahar; Aydemir Guloksuz, Emine Gozde; Yuksel, Mehmet Levent; Turgay, Tahsin Murat; Ates, Askin; Kinikli, Gulay (Sarcoidosis, Vasculitis and Diffuse Lung Diseases, 2023)
Background: Anti-neutrophil cytoplasmic antibody (ANCA)-associated vasculitis (AAV) is a rare autoimmune disease usually involving small vessels and progressing with necrotizing inflammation. Treatment requires long-term use of immunosuppressive agents to inhibit disease activity. Serious infections (SIs) are a common complication in AAV. Objective: The aim of this study was to identify the risk factors for serious infections which required hospitalization in patients with AAV. Methods: In this retrospective cohort study., we included 84 patients admitted to the Ankara University Faculty of Medicine in the last 10 years with a diagnosis of AAV. Results: In 42 (50%) of 84 patients followed up with the diagnosis of AAV, an infection requiring hospitalization was identified. The patients’ total corticosteroid dose, use of pulse steroids, induction regimen, levels of C-reactive protein (CRP) and the presence of pulmonary and renopulmonary involvement were found to be associated with the frequency of infection (p=0.015, p=0.016, p=0.010, p=0.03, p= 0.026 and p=0.029, respectively). In multivariable analysis, it was found that renopulmonary involvement (p=0.002, HR=4.95, 95% CI= 1.804-13.605), age of over 65 (p=0.049, HR=3.37, 95% CI=1.004-11.369) and high CRP levels (p=0.043, HR=1.006, 95% CI=1.000-1.011) constituted independent predictors of serious infection risk. Conclusion: The frequency of infection is known to be increased in ANCA-associated vasculitis. Our study showed that renopulmonary involvement, age and elevated CRP levels on admission are independent risk factors of infection.